2003
DOI: 10.1108/00483480310460180
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the effects of early and late entry on career attainment

Abstract: Literature on tournament mobility in internal labor markets (ILMs) is reviewed revealing a paucity of studies examining the promotion patterns of late entrants into internal promotion systems. An investigation of 502 managers in a large corporation indicated that late entry into the ILM organization was significantly and positively related to career attainment, supporting the “clean slate effect”. In addition, experience in the corporate office was positively related to managerial career attainment, while bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…72 A better powered human kinetic study and a kinetic study using non-human primates, however, showed that the production rate but not the clearance of Lp(a)-apo(a) was significantly reduced following evolocumab or alirocumab treatment, respectively. 75,76 These data concur with the observation that statin treatment has no effect on in normoglycaemic or pre-diabetic patients. Indeed, genetic variation in HMG-CoA reductase and other genes that lower plasma LDL-C levels has been associated with a moderately increased risk of NOD.…”
Section: Odyssey-combo IIsupporting
confidence: 83%
“…72 A better powered human kinetic study and a kinetic study using non-human primates, however, showed that the production rate but not the clearance of Lp(a)-apo(a) was significantly reduced following evolocumab or alirocumab treatment, respectively. 75,76 These data concur with the observation that statin treatment has no effect on in normoglycaemic or pre-diabetic patients. Indeed, genetic variation in HMG-CoA reductase and other genes that lower plasma LDL-C levels has been associated with a moderately increased risk of NOD.…”
Section: Odyssey-combo IIsupporting
confidence: 83%
“…In firms which do not rely so much on ILMs, later entry to managerial careers within the firm becomes possible. An interesting assessment of the relative advantage of early as opposed to late entry is given by Hurley et al (2002), who conclude from their study of US firms that late entry may sometimes be an advantage.…”
Section: Human Resource Developmentmentioning
confidence: 99%
“…Long‐term career paths within the firm are possible but not guaranteed, and late entry is not necessarily a disadvantage in terms of subsequent advancement (and may even be an advantage) (Hurley et al 2002). Advancement is based on rated performance, and reward structures have to be competitive with market rates – with performance‐contingent bonuses a common feature.…”
mentioning
confidence: 99%
“…Deciding to first select a career and then accept promotion(s) are the most common steps that lead to career attainment, or ''the hierarchical level attained in an organization''. 20 Primary predictors of career attainment pinpointed by Hurley et al 21 among top company executives included time spent in line department/functional area, time in the occupation, and breadth of experience. Although not specific to coaching, these leadership environments note that time and experience warrant promotion.…”
Section: Career Decision Makingmentioning
confidence: 99%